Philippine thesaurus on civil law English-Filipino and Filipino-English - Sahagun, Jonas T.; Aguirre, Vyva Victoria M.; Faderon, Rosalie B.; Peregrino, Jovy M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study, Philippine Thesaurus on Civil Law: English-Filipino and Filipino-English, is a pioneering work in the area of Philippine civil law. The thesaurus includes select terms on Philippine civil law covering areas such as persons; family law; property, ownership and its modifications; different modes of acquiring ownership; obligations and contracts; and other peripheral areas. The author focused on the following target objectives: (1) to gather and collate select Philippine civil law terminologies in English and translate these into Filipino; (2) to establish the existing equivalent, associative, and hierarchical relationships of these terminologies; and (3) to promote consistent representation and understanding of subject matter by indexers and researchers on Philippine civil law.
The legal terminologies collected were analyzed using the concept of natural and controlled language relationship and were grouped into broad categories following the deductive or top-down approach. The equivalent, associative, and hierarchical relationships of these terminologies were identified using as guide the arrangement into books, titles, chapters, and subheads of existing Philippine civil laws in the Civil Code of the Philippines. These terminologies were translated from the source language which is English into its nearest equivalent term in a secondary or target language which is Filipino following the concept of degrees of equivalence and non-equivalence using terminological sources in standardized form. Advice of experts from the UP School of Library and Information Studies and the UP Sentro ng Wikang Filipino on legal terms, thesaurus construction, and Filipino language were sought to validate the terms collected and the initial output of the study.
The study resulted into two parts: (1) the Philippine Thesaurus on Civil Law in English consisting of 361 preferred terms and 72 non-preferred terms; and (2) the Philippine Thesaurus on Civil Law in Filipino consisting of 361 preferred terms and 67 non-preferred terms. The following measures are recommended for the thesaurus' continuous development: (1) continuous addition and updating of terminologies and translations; (2) undertaking of test activities by indexers, librarians, and practitioners of select institutions; (3) design and development of an electronic thesaurus manager prototype; and (4) incorporation of the thesaurus into a future study of a more general Philippine Legal thesaurus. The Philippine Thesaurus on Civil Law, being a pioneering study, needs to go through major testing and refinement in the hands of its end users.
Vita.
Thesis (Master of Library and Information Science)
Keywords: Subject headings -- Civil law -- Philippines; English language -- Dictionaries -- Filipino; Filipino language -- Dictionaries -- English